Massive Open Online Course (MOOC) on Medical Entomology - Vasquez Christodoulou, Marlen (My University, 2026)
▪ Insects and arthropods that affect human health (mosquitoes, sandflies, other hematophagous insects and ticks) ▪ Vector-borne diseases and risk mapping (arbovirosis and parasitic diseases: malaria, dengue, Zika, Lyme borreliosis, Chagas disease) ▪ New methods/ concepts to approach vector-borne diseases ▪ Insect immunity and microbiome ▪ Novel approaches for mosquito control Dr Anna-Bella Failloux, Dr Vincent Robert